Binder, negative pole piece, preparation method of negative pole piece, battery and electric device
By using a binder with bimodal particle size distribution, the problem of the risk of demolding between the active material and the current collector is solved and the problem of poor effect of the binder with a single particle size distribution is improved, and the bonding strength and adaptability are improved.
Patent Information
- Application Number
- CN202310876184.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-17
- Publication Date
- 2025-01-17
AI Technical Summary
In the prior art, there is a risk of demolding between the active material and the current collector, which causes the binder to be unable to fully play the bonding role, and the binder with a single particle size distribution is difficult to effectively bond when facing different pores.
By using a binder with at least a bimodal particle size distribution, the binder is ensured to adapt to different pores in the negative electrode coating by mixing the first adhesive polymer and the second adhesive polymer, and the binder and The bonding of the contact point of the active material and the current collector.
The bonding between the adhesive and the active material and the current collector is improved, the bonding site is increased, the bonding strength is improved, and the bonding effect is adapted to the bonding effect of different pores.
Smart Images

Figure CN119324228A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a binder, a negative electrode sheet and a preparation method thereof, a battery and an electrical device. Background Art
[0002] With the rapid growth of portable electronic devices and electric vehicles, the demand for power batteries is also growing. Among them, the electrochemical performance of batteries is also attracting more and more attention.
[0003] Currently, there is a risk of demolding between the active material and the current collector. Summary of the invention
[0004] The main purpose of the present invention is to provide a binder to improve the bonding between the active material and the current collector.
[0005] To achieve the above object, the present invention provides a binder having at least a bimodal particle size distribution.
[0006] The binder has at least a bimodal particle size distribution. Considering that the negative electrode coating includes pores of different sizes, the binder has at least a bimodal particle size distribution, which improves the contact between the binder and the material around the pores of the negative electrode coating, thereby improving the bonding sites between the binder and the active material, and improving the bonding between the current collector and the active material.
[0007] Bimodal particle size distribution: The particle size distribution of the binder is tested using a particle size analyzer to obtain a particle size distribution graph. Two particle size peaks are observed in the graph, indicating that the viscous polymer has a bimodal particle size distribution.
[0008] It can be understood that the particle size distribution of the binder is tested by a particle size analyzer to obtain a particle size distribution graph, in which at least two particle size distribution peaks are observed.
[0009] It is understandable that if the binder is all small and uniform in size, when facing large pores, the binder may be directly contained in the large pores, making it difficult to bond the materials around the large pores together. If the binder is all large and uniform in size, the number of binder particles is reduced under the same mass, and the bonding sites are reduced. Binders with a single particle size distribution cannot fully exert their bonding effect.
[0010] Optionally, the adhesive includes a first viscous polymer and a second viscous polymer, and the Dv50 value of the first viscous polymer is defined as D1, and the Dv50 value of the second viscous polymer is defined as D2, satisfying D1<D2, preferably, 0nm<(D2-D1)≤390nm, and further preferably, 100nm≤(D2-D1)≤350nm;
[0011] And / or, the adhesive comprises a first viscous polymer, and a Dv50 value of the first viscous polymer is defined as D1, satisfying 10nm≤D1<150nm, preferably, 50nm≤D1<150nm;
[0012] And / or, the adhesive includes a second viscous polymer, the Dv50 value of the second viscous polymer is D2, and satisfies 150nm≤D2≤400nm.
[0013] Dv50 of the first viscous polymer is the particle size corresponding to when the cumulative particle size distribution percentage of the first viscous polymer sample reaches 50%. Its physical meaning is that 50% of the total volume of particles have a diameter greater than this value, and the other 50% of the total volume of particles have a diameter less than this value. Dv50 is often used to indicate the median particle size of a powder.
[0014] When the particle size distribution is normally distributed or shows obvious symmetrical distribution around Dv50, the average value = Dv50.
[0015] It can be understood that in the preparation process of the adhesive, the first adhesive polymer and the second adhesive polymer are mixed to obtain the adhesive, and the first adhesive polymer and the second adhesive polymer have different Dv50, so that after the first adhesive polymer and the second adhesive polymer are mixed, the obtained adhesive has at least a bimodal particle size distribution.
[0016] Furthermore, D1<D2, preferably, 0nm<(D2-D1)≤390nm, further preferably, 100nm≤(D2-D1)≤350nm; and / or, the adhesive includes a first adhesive polymer, and the Dv50 value of the first adhesive polymer is defined as D1, satisfying 10nm≤D1<150nm, preferably, 50nm≤D1<150nm; and / or, the adhesive includes a second adhesive polymer, and the Dv50 value of the second adhesive polymer is D2, satisfying 150nm≤D2≤400nm. By satisfying the relationship between D1 of the first adhesive polymer and D2 of the second adhesive polymer, the adhesive performance of the adhesive can be improved.
[0017] Optionally, the at least bimodal particle size distribution comprises a first particle size peak and a second particle size peak, the first particle size peak is smaller than the second particle size peak, preferably, the range value of the difference between the first particle size peak and the second particle size peak is greater than 0 nm and less than or equal to 390 nm, preferably, 100 nm to 350 nm;
[0018] And / or, the at least bimodal particle size distribution comprises a first particle size peak value, the first particle size peak value has a range value of greater than or equal to 10 nm and less than 150 nm, preferably, greater than or equal to 50 nm and less than 150 nm;
[0019] And / or, the at least bimodal particle size distribution comprises a second particle size peak, wherein the second particle size peak has a value in the range of 150 nm to 400 nm.
[0020] The first particle size peak and the second particle size peak. The particle size distribution of the binder is tested by a particle size analyzer to obtain a particle size distribution graph. In the graph, two particle size distribution peaks are observed, one particle size distribution peak has a first particle size peak, and the other particle size distribution peak has a second particle size peak.
[0021] Peak value, that is, its physical meaning is that 50% of the particles in the total volume of this particle size distribution have a diameter greater than this value, and another 50% of the particles in the total volume of this particle size distribution have a diameter less than this value. Dv50 is often used to indicate the median particle size of a powder.
[0022] Preferably, the range value of the difference between the first particle size peak and the second particle size peak is greater than 0nm and less than or equal to 390nm, preferably, 100nm to 350nm; and / or, at least the bimodal particle size distribution includes the first particle size peak, the range value of the first particle size peak is greater than or equal to 10nm and less than 150nm, preferably, greater than or equal to 50nm and less than 150nm; and / or, at least the bimodal particle size distribution includes the second particle size peak, the range value of the second particle size peak is 150nm to 400nm. At least the bimodal particle size distribution includes the first particle size peak and the second particle size peak, the first particle size peak is less than the second particle size peak, the first particle size peak and the second particle size peak meet the above range, that is, the particle size of the binder meets the large particle size range and the small particle size range, which can improve the bonding between the current collector and the active material.
[0023] Optionally, the adhesive further includes a third viscous polymer, the Dv50 value of the third viscous polymer is D3, satisfying D2<D3, preferably, 0nm<(D3-D2)≤850nm, further preferably, 250nm≤(D3-D2)≤650nm;
[0024] And / or, the adhesive further includes a third viscous polymer, the Dv50 value of the third viscous polymer is D3, and satisfies 400nm<D3≤1000nm, preferably, 400nm<D3≤800nm.
[0025] It can be understood that in the preparation process of the adhesive, the first viscous polymer, the second viscous polymer, and the third viscous polymer are mixed to obtain the adhesive, and the first viscous polymer, the second viscous polymer, and the third viscous polymer have different Dv50, so that after the first viscous polymer, the second viscous polymer, and the third viscous polymer are mixed, the obtained adhesive has at least a trimodal particle size distribution.
[0026] Furthermore, D1<D2, preferably, 0nm<(D2-D1)≤390nm, more preferably, 100nm≤(D2-D1)≤350nm; D2<D3, preferably, 0nm<(D3-D2)≤850nm, more preferably, 250nm≤(D3-D2)≤650nm, and / or, the range value of D3 of the third adhesive polymer is 400nm<D3≤1000nm, preferably, 400nm<D3≤800nm. By satisfying the relationship among D1 of the first adhesive polymer, D2 of the second adhesive polymer, and D3 of the third adhesive polymer, the adhesive performance of the binder can be improved, and the adhesiveness between the current collector and the active material can be improved.
[0027] That is, the particle size of the binder satisfies the large particle size range, the medium particle size range, and the small particle size range, which can improve the adhesion between the current collector and the active material.
[0028] Optionally, the at least bimodal particle size distribution further comprises a third particle size peak value, the third particle size peak value is greater than the second particle size peak value, preferably, the range value of the difference between the third particle size peak value and the second particle size peak value is greater than 0 nm and less than or equal to 850 nm, preferably, 250 nm to 650 nm;
[0029] And / or, the at least bimodal particle size distribution further includes a third particle size peak value, the range value of the third particle size peak value is greater than 400 nm and less than or equal to 1000 nm, preferably, greater than 400 nm and less than or equal to 800 nm.
[0030] The range value of the first particle size peak is greater than or equal to 10nm and less than 150nm, preferably, greater than or equal to 50nm and less than 150nm, the range value of the second particle size peak is 150nm to 400nm, and the range value of the third particle size peak is greater than 400nm and less than or equal to 1000nm, preferably, greater than 400nm and less than or equal to 800nm. At least a bimodal particle size distribution includes a first particle size peak, a second particle size peak, and a third particle size peak, the first particle size peak is less than the second particle size peak, the third particle size peak is greater than the second particle size peak, the first particle size peak, the second particle size peak, and the third particle size peak meet the above range, that is, the particle size of the binder meets the large particle size range, the medium particle size range, and the small particle size range, which can improve the bonding between the current collector and the active material.
[0031] Optionally, the mass of the first viscous polymer is defined as m1, and the mass of the second viscous polymer is defined as m2, then m1 / m2=1 / 9 to 9, preferably, m1 / m2=1 / 3 to 3.
[0032] It is understood that the binder of the present application includes a first viscous polymer and a second viscous polymer. For example, in one embodiment, the mass of the first viscous polymer is m1, and the mass of the second viscous polymer is m2, then m1 / m2=1 / 9 to 9, preferably, m1 / m2=1 / 3 to 3. It is understood that by mixing the first viscous polymer and the second viscous polymer according to the above mass ratio to obtain a binder, the bonding between the current collector and the active material can be improved.
[0033] Optionally, the mass of the third viscous polymer is defined as m3, then (m1+m2) / m3=1 / 9 to 9, preferably, (m1+m2) / m3=1 / 3 to 3.
[0034] It can be understood that the adhesive of the present application includes a first viscous polymer, a second viscous polymer, and a third viscous polymer. For example, in one embodiment, the mass of the first viscous polymer is m1, the mass of the second viscous polymer is m2, and the mass of the third viscous polymer is m3, then (m1+m2) / m3=1 / 9 to 9, preferably, (m1+m2) / m3=1 / 3 to 3.
[0035] It can be understood that the masses of the first viscous polymer, the second viscous polymer and the third viscous polymer meet the above range, and the binder obtained by mixing the first viscous polymer, the second viscous polymer and the third viscous polymer can improve the adhesion between the current collector and the active material.
[0036] It can be understood that, in theory, the negative electrode coating has a certain porosity. When the mass ratio of the first viscous polymer, the second viscous polymer, and the third viscous polymer meets the above range value, the bonding site between the binder and the negative electrode coating is improved, and the bonding performance is better; for example, for the same kind of hard carbon, the larger the particle size, the greater the porosity, and the larger the gap. At this time, the mass of the third viscous polymer with a large particle size is increased to improve the contact between the third viscous polymer with a large particle size and the hard carbon around the large gap, thereby improving the bonding performance.
[0037] Optionally, the binder has a glass transition temperature of -50°C to 60°C, preferably, -40°C to 30°C.
[0038] The glass transition temperature of the binder satisfies the above range, which can improve the flexibility of the current collector after coating with the binder.
[0039] Optionally, the adhesive polymer includes at least one of polyvinylidene fluoride polymers, acrylonitrile polymers, styrene acrylic polymers, pure acrylic polymers, and styrene butadiene polymers, preferably, includes styrene butadiene polymers and / or styrene acrylic polymers.
[0040] The first adhesive polymer, the second adhesive polymer and the third adhesive polymer in the present application include but are not limited to at least one of polyvinylidene fluoride polymers, acrylonitrile polymers, styrene acrylic polymers, pure acrylic polymers and styrene butadiene polymers, preferably, they include styrene butadiene polymers and / or styrene acrylic polymers. Styrene butadiene polymers and styrene acrylic polymers have better adhesion and flexibility.
[0041] That is, the first viscous polymer, the second viscous polymer, and the third viscous polymer may be the same polymer, or they may be different polymers, which can be set according to actual needs.
[0042] Optionally, the constituent monomers of the polyvinylidene fluoride polymer include vinylidene fluoride, or further include at least one of hexafluoropropylene, pentafluoropropylene, tetrafluoropropylene, trifluoropropylene, perfluorobutene, tetrafluoroethylene, trifluoroethylene, trifluorochloroethylene, and vinyl fluoride;
[0043] And / or, the monomers constituting the acrylonitrile polymer include acrylonitrile, or further include at least one of acrylates, acrylamides, vinyl esters, vinyl ethers, vinyl amides, vinyl ketones, styrenes, halogen-containing monomers (such as trichloroacetyl or tribromoacetyl), ionic monomers (2-acrylamide-2-methylpropane sulfonic acid monomers), and basic monomers (4-vinyl-{3-sulfopropyl)pyridine indinate);
[0044] And / or, the constituent monomers of the styrene acrylic polymer include styrene and acrylic acid;
[0045] And / or, the constituent monomers of the pure acrylic polymer include acrylic acid;
[0046] And / or, the constituent monomers of the styrene-butadiene polymer include styrene and butadiene.
[0047] The constituent monomers of the polyvinylidene fluoride polymers in the present application include vinylidene fluoride, for example, it can be a vinylidene fluoride homopolymer, and homopolymerization refers to a polymerization reaction carried out by an organic monomer; of course, it can also be a copolymer formed by copolymerization of vinylidene fluoride with at least one of hexafluoropropylene, pentafluoropropylene, tetrafluoropropylene, trifluoropropylene, perfluorobutene, tetrafluoroethylene, trifluoroethylene, chlorotrifluoroethylene, and vinyl fluoride, and copolymerization refers to a reaction in which two or more compounds are polymerized into one substance under certain conditions.
[0048] The constituent monomers of the acrylonitrile polymer in the present application include acrylonitrile, for example, it can be an acrylonitrile homopolymer, and homopolymerization refers to a polymerization reaction carried out by one organic monomer; of course, it can also be a copolymer formed by copolymerization of acrylonitrile with at least one of acrylates, acrylamides, vinyl esters, vinyl ethers, vinyl amides, vinyl ketones, styrenes, halogen-containing monomers, ionic monomers, and basic monomers, and copolymerization refers to a reaction in which two or more compounds are polymerized into one substance under certain conditions.
[0049] The constituent monomers of the styrene acrylic polymer in the present application include styrene and acrylic acid, and of course other types of monomers may also be included to modify it, without specific limitation.
[0050] The constituent monomers of the pure acrylic polymer in the present application include acrylic acid, for example, it can be acrylic acid homopolymer, and of course it can also include other monomers, which are modified, and there is no specific limitation.
[0051] The constituent monomers of the styrene-butadiene polymer in the present application include styrene and butadiene, and of course other types of monomers may also be included to modify it, without specific limitation.
[0052] Optionally, the constituent monomers of the polyvinylidene fluoride polymer include vinylidene fluoride and hexafluoropropylene, and the molar ratio of the vinylidene fluoride to the hexafluoropropylene is 1:(0.03 to 0.5), preferably 1:(0.03 to 0.2);
[0053] And / or, the constituent monomers of the styrene acrylic polymer include styrene and acrylic acid, and the molar ratio of the styrene to the acrylic acid is 5 / 1 to 1 / 5, preferably 2 / 1 to 1 / 2;
[0054] And / or, the constituent monomers of the styrene-butadiene polymer include styrene and butadiene, and the molar ratio of the styrene to the butadiene is 3 / 1 to 1 / 3, preferably 1.5 / 1 to 1 / 1.5.
[0055] For example, in one embodiment, the constituent monomers of the polyvinylidene fluoride polymer include vinylidene fluoride and hexafluoropropylene, and the molar ratio of vinylidene fluoride to hexafluoropropylene is 1:(0.03 to 0.5), preferably, 1:(0.03 to 0.2); in one embodiment, the constituent monomers of the styrene acrylic polymer include styrene and acrylic acid, and the molar ratio of styrene to acrylic acid is 5 / 1 to 1 / 5, preferably, 2 / 1 to 1 / 2; in one embodiment, the constituent monomers of the butadiene polymer include styrene and butadiene, and the molar ratio of styrene to butadiene is 3 / 1 to 1 / 3, preferably, 1.5 / 1 to 1 / 1.5.
[0056] Optionally, the adhesive polymer comprises an emulsion type.
[0057] It can be understood that the first viscous polymer, the second viscous polymer, and the third viscous polymer respectively include but are not limited to emulsion types. The emulsion type refers to an emulsion state formed by the viscous polymer being dispersed in a dispersion medium (such as water) under the action of an emulsifier. The emulsion state has a good dispersion effect, and it is difficult for particles to agglomerate, which helps to evenly mix the slurry.
[0058] The present application also provides a negative electrode plate, which comprises a current collector, a primer layer and a negative electrode coating in sequence along a thickness direction, and the primer layer comprises the binder as claimed in claim 1.
[0059] It can be understood that an active layer is formed by preparing a slurry of a binder, an active material, etc. and applying it to a current collector. Due to the evaporation of the solvent during the coating process, the binder tends to float under the action of capillary forces, surface tension, and concentration gradients. Binder floating refers to the redistribution of the evenly dispersed binder, so that the binder content in the place in contact with the current collector is reduced, and the binder floats to the surface of the slurry, resulting in insufficient bonding between the active material and the current collector, and there is a risk of demolding.
[0060] In order to improve the above problems, the present application directly uses a primer layer, which includes a binder. Compared with the active layer, the primer layer is thinner and there is no problem of the binder floating.
[0061] It can be understood that hard carbon particles are poorly regular and contain a large number of pores. The binder used in the present application has at least a bimodal particle size distribution. In the case of the same mass of binder, the binder with at least a bimodal particle size distribution forms more bonding sites. For example, in the bimodal particle size distribution, the particle size peak a is less than the particle size peak b. The binder with a bimodal particle size distribution includes a particle size peak a and a particle size peak b. The mass of the binder including the particle size peak a and the particle size peak b is the same as the mass of the binder with only the particle size peak b. At this time, the number of particles of the binder with a bimodal particle size distribution including the particle size peak a and the particle size peak b is greater than the number of particles of the binder with a unimodal particle size distribution including only the particle size peak b. When the binder is evenly dispersed, the more binder particles there are, the more bonding sites are formed, which is beneficial to improving the bonding strength. In addition, the hard carbon pores include pores of different sizes. The binder with a single particle size distribution is difficult to play a bonding role when facing large pores. Therefore, a binder with at least a bimodal particle size distribution is used so that the binder can exert better bonding properties when facing different pores.
[0062] Optionally, the thickness of the primer layer ranges from 1 um to 5 um, preferably from 1.5 um to 3 um.
[0063] The thickness of the undercoat layer satisfying the above range can improve the binding force between the active material and the current collector.
[0064] Optionally, the mass of the binder in the primer layer accounts for 10% to 70% of the total mass of the primer layer, preferably, 20% to 50%.
[0065] The percentage of the mass of the binder in the primer layer to the total mass of the primer layer satisfies the above range, which can improve the bonding performance of the binder. Specifically, when the mass of the binder accounts for too small a percentage of the total mass of the primer layer, the problem of poor adhesion is improved, and when the mass of the binder accounts for too large a percentage of the total mass of the primer layer, the problem of deteriorated conductivity between the current collector and the active layer is improved.
[0066] Optionally, the base coating layer includes a conductive agent, a dispersant and the binder, and the mass ratio of the conductive agent, the dispersant and the binder is in the range of (30 to 80): (1 to 10): (10 to 70).
[0067] The primer layer includes a conductive agent, a dispersant and a binder. The mass ratio of the conductive agent, the dispersant and the binder satisfies the above range, which can improve the conductivity and adhesion of the primer layer.
[0068] Optionally, the porosity of the negative electrode coating ranges from 30% to 70%, preferably, from 35% to 60%.
[0069] The porosity range of the negative electrode coating satisfies the above range, which can improve the bonding between the negative electrode material and the current collector.
[0070] The present application also provides a method for preparing a negative electrode sheet; comprising:
[0071] Mixing a conductive agent, a dispersant, and a binder to prepare a primer slurry;
[0072] Applying the primer slurry to the current collector to obtain a primer layer;
[0073] The negative electrode slurry is applied to the undercoat layer to obtain a negative electrode sheet.
[0074] In the process of preparing the negative electrode sheet, a conductive agent, a dispersant and a binder are mixed to prepare a primer slurry; the primer slurry is applied to the current collector to obtain a primer layer; and the negative electrode slurry is applied to the primer layer to obtain a negative electrode sheet.
[0075] The present application also provides a battery, which includes the negative electrode plate as described above; or includes the negative electrode plate obtained by the method for preparing the negative electrode plate as described above.
[0076] The present application also provides an electrical device, which includes the battery as described.
[0077] The binder of the present application has at least a bimodal particle size distribution. Considering that the negative electrode coating includes pores of different sizes, the binder has at least a bimodal particle size distribution, which improves the contact between the binder and the material around the pores of the negative electrode coating, thereby improving the bonding site between the binder and the active material, and improving the bonding between the current collector and the active material. BRIEF DESCRIPTION OF THE DRAWINGS
[0078] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0079] Figure 1 It is a schematic diagram of a process flow of preparing a negative electrode sheet according to an embodiment of the present application;
[0080] Figure 2 It is a schematic structural diagram of a negative electrode sheet according to an embodiment of the present application;
[0081] Figure 3 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0082] Figure 4 yes Figure 3 An exploded view of a secondary battery according to an embodiment of the present application is shown;
[0083] Figure 5 is a schematic diagram of a battery module according to an embodiment of the present application;
[0084] Figure 6 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0085] Figure 7 yes Figure 6 An exploded view of a battery pack according to an embodiment of the present application is shown;
[0086] Figure 8 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0087] Description of Figure Numbers:
[0088] Label name Label name 1 Battery Pack 5 Secondary battery 2 Upper box 51 case 3 Lower box 52 Electrode assembly 4 Battery Module 53 Top cover assembly 10 current collector 20 Base coating 30 Anode coating 100 Negative electrode
[0089] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0090] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0091] Hereinafter, the binder, negative electrode sheet and preparation method thereof, battery and electric device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0092] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0093] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0094] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0095] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0096] With the rapid growth of portable electronic devices, electric vehicles, etc., the demand for power batteries is also growing. Among them, the electrochemical performance of batteries is also attracting more and more attention. At present, there is a risk of demolding between the active material and the current collector. For example, there are a lot of gaps between the active material and the current collector, which makes the binder with a single particle size distribution unable to fully play its due bonding role.
[0097] In order to solve the above problems, the present application proposes a binder having at least a bimodal particle size distribution.
[0098] Binder refers to a material with adhesive properties that is used to bond different substances together.
[0099] Polymer is a product formed by polymerization (addition polymerization) of monomers.
[0100] Sticky polymer, a polymer having sticky properties.
[0101] Bimodal particle size distribution: The particle size distribution of the binder is tested using a particle size analyzer to obtain a particle size distribution graph. Two peaks are observed in the graph, indicating that the viscous polymer has a bimodal particle size distribution.
[0102] The binder has at least a bimodal particle size distribution. Considering that the negative electrode coating includes pores of different sizes, the binder has at least a bimodal particle size distribution, which improves the contact between the binder and the material around the pores of the negative electrode coating, thereby improving the bonding sites between the binder and the active material, and improving the bonding between the current collector and the active material.
[0103] It can be understood that the particle size distribution of the binder is tested by a particle size analyzer to obtain a particle size distribution graph, in which at least two particle size distribution peaks are observed.
[0104] It is understandable that if the binder is all small and uniform in size, when facing large pores, the binder may be directly contained in the large pores, making it difficult to bond the materials around the large pores together. If the binder is all large and uniform in size, the number of binder particles is reduced under the same mass, and the bonding sites are reduced. Binders with a single particle size distribution cannot fully exert their bonding effect.
[0105] In one embodiment, the adhesive includes a first viscous polymer and a second viscous polymer, and the Dv50 value of the first viscous polymer is defined as D1, and the Dv50 value of the second viscous polymer is defined as D2, satisfying D1<D2, preferably, 0nm<(D2-D1)≤390nm, and further preferably, 100nm≤(D2-D1)≤350nm; and / or, the adhesive includes the first viscous polymer, and the Dv50 value of the first viscous polymer is defined as D1, satisfying 10nm≤D1<150nm, preferably, 50nm≤D1<150nm; and / or, the adhesive includes the second viscous polymer, and the Dv50 value of the second viscous polymer is D2, satisfying 150nm≤D2≤400nm.
[0106] Dv50 of the first viscous polymer is the particle size corresponding to when the cumulative particle size distribution percentage of the first viscous polymer sample reaches 50%. Its physical meaning is that 50% of the total volume of particles have a diameter greater than this value, and the other 50% of the total volume of particles have a diameter less than this value. Dv50 is often used to indicate the median particle size of a powder.
[0107] When the particle size distribution is normally distributed or shows obvious symmetrical distribution around Dv50, the average value = Dv50.
[0108] Dv50 can be tested by methods known in the art. For example, GB / T19077-2016 can be referred to, and a Malvern laser particle size analyzer can be used for characterization testing, such as a Malvern Mastersizer-3000 or other instrument.
[0109] It can be understood that in the preparation process of the adhesive, the first adhesive polymer and the second adhesive polymer are mixed to obtain the adhesive, and the first adhesive polymer and the second adhesive polymer have different volume average particle sizes, so that after the first adhesive polymer and the second adhesive polymer are mixed, the obtained adhesive has at least a bimodal particle size distribution.
[0110] Furthermore, D1<D2, preferably, 0nm<(D2-D1)≤390nm, further preferably, 100nm≤(D2-D1)≤350nm; and / or, the adhesive includes a first adhesive polymer, and the Dv50 value of the first adhesive polymer is defined as D1, satisfying 10nm≤D1<150nm, preferably, 50nm≤D1<150nm; and / or, the adhesive includes a second adhesive polymer, and the Dv50 value of the second adhesive polymer is D2, satisfying 150nm≤D2≤400nm. By satisfying the relationship between D1 of the first adhesive polymer and D2 of the second adhesive polymer, the adhesive performance of the adhesive can be improved.
[0111] In the above 0nm<(D2-D1)≤390nm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 1nm, 5nm, 10nm, 20nm, 30nm, 50nm, 80nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 390nm, etc., and the range values between any two of the above point values.
[0112] In the above 100nm≤(D2-D1)≤350nm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 100nm, 120nm, 150nm, 170nm, 200nm, 120nm, 250nm, 270nm, 300nm, 350nm, etc., and the range values between any two of the above point values.
[0113] In one embodiment, the at least bimodal particle size distribution includes a first particle size peak and a second particle size peak, the first particle size peak is smaller than the second particle size peak, preferably, the range value of the difference between the first particle size peak and the second particle size peak is greater than 0nm and less than or equal to 390nm, preferably, 100nm to 350nm; and / or, the at least bimodal particle size distribution includes a first particle size peak, the range value of the first particle size peak is greater than or equal to 10nm and less than 150nm, preferably, greater than or equal to 50nm and less than 150nm; and / or, the at least bimodal particle size distribution includes a second particle size peak, the range value of the second particle size peak is 150nm to 400nm.
[0114] The first particle size peak and the second particle size peak. The particle size distribution of the binder is tested by a particle size analyzer to obtain a particle size distribution graph. In the graph, two particle size distribution peaks are observed, one particle size distribution peak has a first particle size peak, and the other particle size distribution peak has a second particle size peak.
[0115] Preferably, the range value of the difference between the first particle size peak and the second particle size peak is greater than 0nm and less than or equal to 390nm, preferably, 100nm to 350nm; and / or, at least the bimodal particle size distribution includes the first particle size peak, the range value of the first particle size peak is greater than or equal to 10nm and less than 150nm, preferably, greater than or equal to 50nm and less than 150nm; and / or, at least the bimodal particle size distribution includes the second particle size peak, the range value of the second particle size peak is 150nm to 400nm. At least the bimodal particle size distribution includes the first particle size peak and the second particle size peak, the first particle size peak is less than the second particle size peak, the first particle size peak and the second particle size peak meet the above range, that is, the particle size of the binder meets the large size distribution and the small size distribution, which can improve the bonding between the current collector and the active material.
[0116] In the above-mentioned range greater than or equal to 10nm and less than 150nm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 10nm, 20nm, 30nm, 50nm, 80nm, 100nm, 149nm, etc., and the range values between any two of the above-mentioned point values.
[0117] In the above-mentioned range greater than or equal to 50nm and less than 150nm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 50nm, 80nm, 100nm, 149nm, 149nm, etc., and the range values between any two of the above-mentioned point values.
[0118] In the above-mentioned 150nm to 400nm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 150nm, 180nm, 200nm, 250nm, 300nm, 350nm, 400nm, etc., and the range values between any two of the above-mentioned point values.
[0119] In the above-mentioned range greater than 0nm and less than or equal to 390nm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 1nm, 5nm, 10nm, 20nm, 30nm, 50nm, 80nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 390nm, etc., and the range values between any two of the above-mentioned point values.
[0120] In one embodiment, the adhesive further includes a third viscous polymer, the Dv50 value of the third viscous polymer is D3, satisfying D2<D3, preferably, 0nm<(D3-D2)≤850nm, and further preferably, 250nm≤(D3-D2)≤650nm ; And / or, the adhesive further includes a third viscous polymer, the Dv50 value of the third viscous polymer is D3, and satisfies 400nm<D3≤1000nm, preferably, 400nm<D3≤800nm.
[0121] It can be understood that in the preparation process of the adhesive, the first viscous polymer, the second viscous polymer, and the third viscous polymer are mixed to obtain the adhesive, and the first viscous polymer, the second viscous polymer, and the third viscous polymer have different Dv50, so that after the first viscous polymer, the second viscous polymer, and the third viscous polymer are mixed, the obtained adhesive has at least a trimodal particle size distribution.
[0122] Furthermore, D1<D2, preferably, 0nm<(D2-D1)≤390nm, more preferably, 100nm≤(D2-D1)≤350nm; D2<D3, preferably, 0nm<(D3-D2)≤850nm, more preferably, 250nm≤(D3-D2)≤650nm, and / or, the range value of D3 of the third adhesive polymer is 400nm<D3≤1000nm, preferably, 400nm<D3≤800nm. By satisfying the relationship among D1 of the first adhesive polymer, D2 of the second adhesive polymer, and D3 of the third adhesive polymer, the adhesive performance of the binder can be improved, and the adhesiveness between the current collector and the active material can be improved.
[0123] That is, the particle sizes of the binder satisfy the large particle size range, the medium particle size range, and the small particle size range, respectively, which can improve the adhesion between the current collector and the active material.
[0124] In the above 0nm<(D3-D2)≤850nm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 1nm, 5nm, 10nm, 20nm, 30nm, 50nm, 80nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 390nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 775nm, 800nm, 850nm, etc., and the range value between any two of the above point values.
[0125] In the above 250nm≤(D3-D2)≤650nm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 250nm, 300nm, 350nm, 390nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, etc., and the range values between any two of the above point values.
[0126] In one embodiment, the at least bimodal particle size distribution includes a third particle size peak, the third particle size peak is greater than the second particle size peak, preferably, the range value of the difference between the third particle size peak and the second particle size peak is greater than 0nm and less than or equal to 850nm, preferably, 250nm to 650nm; and / or, the at least bimodal particle size distribution also includes a third particle size peak, the range value of the third particle size peak is greater than 400nm and less than or equal to 1000nm, preferably, greater than 400nm and less than or equal to 800nm.
[0127] The range value of the first particle size peak is greater than or equal to 10nm and less than 150nm, preferably, greater than or equal to 50nm and less than 150nm, the range value of the second particle size peak is 150nm to 400nm, and the range value of the third particle size peak is greater than 400nm and less than or equal to 1000nm, preferably, greater than 400nm and less than or equal to 800nm. At least a bimodal particle size distribution includes a first particle size peak, a second particle size peak, and a third particle size peak, the first particle size peak is less than the second particle size peak, the third particle size peak is greater than the second particle size peak, the first particle size peak, the second particle size peak, and the third particle size peak meet the above range, that is, the particle size of the binder meets the large particle size range, the medium particle size range, and the small particle size range, which can improve the bonding between the current collector and the active material.
[0128] In the above-mentioned range greater than 400nm and less than or equal to 1000nm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 410nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 775nm, 800nm, 1000nm, etc., and the range values between any two of the above-mentioned point values.
[0129] In the above-mentioned range greater than 400nm and less than or equal to 800nm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 410nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 775nm, 800nm, etc., and the range values between any two of the above-mentioned point values.
[0130] In the above-mentioned range greater than 0nm and less than or equal to 850nm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 1nm, 5nm, 10nm, 20nm, 30nm, 50nm, 80nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 390nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 775nm, 800nm, 850nm, etc., and the range value between any two of the above-mentioned point values.
[0131] In one embodiment, the mass of the first viscous polymer is defined as m1, and the mass of the second viscous polymer is defined as m2, then m1 / m2=1 / 9 to 9, preferably, m1 / m2=1 / 3 to 3.
[0132] It is understood that the binder of the present application includes a first viscous polymer and a second viscous polymer. For example, in one embodiment, the mass of the first viscous polymer is m1, and the mass of the second viscous polymer is m2, then m1 / m2=1 / 9 to 9, preferably, m1 / m2=1 / 3 to 3. It is understood that by mixing the first viscous polymer and the second viscous polymer according to the above mass ratio to obtain a binder, the bonding between the current collector and the active material can be improved.
[0133] In one embodiment, the mass of the third viscous polymer is defined as m3, then (m1+m2) / m3=1 / 9 to 9, preferably, (m1+m2) / m3=1 / 3 to 3.
[0134] It can be understood that the adhesive of the present application includes a first viscous polymer, a second viscous polymer, and a third viscous polymer. For example, in one embodiment, the mass of the first viscous polymer is m1, the mass of the second viscous polymer is m2, and the mass of the third viscous polymer is m3, then (m1+m2) / m3=1 / 9 to 9, preferably, (m1+m2) / m3=1 / 3 to 3.
[0135] It can be understood that the binder obtained by mixing the first viscous polymer, the second viscous polymer, and the third viscous polymer can improve the adhesion between the current collector and the active material.
[0136] It can be understood that, in theory, the negative electrode coating has a certain porosity. When the mass ratio of the first viscous polymer, the second viscous polymer, and the third viscous polymer meets the above range value, the bonding site between the binder and the negative electrode coating is improved, and the bonding performance is better; for example, for the same kind of hard carbon, the larger the particle size, the greater the porosity, and the larger the gap. At this time, the mass of the third viscous polymer is adjusted to increase, improve the contact between the third viscous polymer with a large particle size distribution and the hard carbon around the large gap, and improve the bonding performance.
[0137] In the above 1 / 9 to 9, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 1 / 9, 2 / 9, 3 / 9, 4 / 9, 5 / 9, 6 / 9, 7 / 9, 8 / 9, 1, 2, 3, 4, 5, 6, 7, 8, 9, etc., as well as the range values between any two of the above point values.
[0138] In one embodiment, the glass transition temperature of the binder is -50°C to 60°C, preferably, -40°C to 30°C.
[0139] The glass transition temperature is the temperature at which a polymer changes from a highly elastic state to a glassy state. It refers to the transition temperature of an amorphous polymer (including the non-crystalline part of a crystalline polymer) from a glassy state to a highly elastic state or from the latter to the former. It is the lowest temperature at which the macromolecular segments of an amorphous polymer can move freely, and is usually represented by Tg. Above the glass transition temperature, the polymer exhibits elasticity; below the glass transition temperature, the polymer exhibits brittleness. The glass transition temperature can be measured by methods commonly used in the art, for example, it can be tested by differential scanning calorimetry with reference to GB / T19466.2.
[0140] The glass transition temperature of the binder satisfies the above range, which can improve the flexibility of the current collector after coating with the binder.
[0141] In the above-mentioned -50℃ to 60℃, the values include the minimum and maximum values of the range, and every value between such minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and -50℃, -40℃, -30℃, -20℃, -10℃, 0℃, 10℃, 20℃, 30℃, 40℃, 50℃, 60℃, etc., and the range values between any two of the above-mentioned point values.
[0142] In one embodiment, the viscous polymer includes at least one of polyvinylidene fluoride polymers, acrylonitrile polymers, styrene acrylic polymers, pure acrylic polymers, and styrene butadiene polymers, preferably, includes styrene butadiene polymers and / or styrene acrylic polymers.
[0143] Polyvinylidene fluoride polymer, the structural formula includes
[0144] Acrylonitrile polymers, the structural formula includes
[0145] Styrene acrylic polymer, the polymerization monomers include styrene and acrylate monomers.
[0146] Pure acrylic polymer, the polymerization monomer includes acrylic acid, and of course can also include acrylates, methacrylates, etc.
[0147] Butadiene-styrene polymers, the polymerization monomers include butadiene and styrene.
[0148] The first adhesive polymer, the second adhesive polymer and the third adhesive polymer in the present application include but are not limited to at least one of polyvinylidene fluoride polymers, acrylonitrile polymers, styrene acrylic polymers, pure acrylic polymers and styrene butadiene polymers, preferably, they include styrene butadiene polymers and / or styrene acrylic polymers. Styrene butadiene polymers and styrene acrylic polymers have better adhesion and flexibility.
[0149] That is, the first viscous polymer, the second viscous polymer, and the third viscous polymer may be the same polymer, or they may be different polymers, which can be set according to actual needs.
[0150] In one embodiment, the constituent monomers of the polyvinylidene fluoride polymer include vinylidene fluoride, or also include at least one of hexafluoropropylene, pentafluoropropylene, tetrafluoropropylene, trifluoropropylene, perfluorobutene, tetrafluoroethylene, trifluoroethylene, chlorotrifluoroethylene, and vinyl fluoride; and / or, the constituent monomers of the acrylonitrile polymer include acrylonitrile, or also include at least one of acrylates, acrylamides, vinyl esters, vinyl ethers, vinyl amides, vinyl ketones, styrenes, halogen-containing monomers, ionic monomers, and basic monomers; and / or, the constituent monomers of the styrene-acrylic polymer include styrene and acrylic acid; and / or, the constituent monomers of the pure acrylic polymer include acrylic acid; and / or, the constituent monomers of the styrene-butadiene polymer include styrene and butadiene.
[0151] The constituent monomers of the polyvinylidene fluoride polymers in the present application include vinylidene fluoride, for example, it can be a vinylidene fluoride homopolymer, and homopolymerization refers to a polymerization reaction carried out by an organic monomer; of course, it can also be a copolymer formed by copolymerization of vinylidene fluoride with at least one of hexafluoropropylene, pentafluoropropylene, tetrafluoropropylene, trifluoropropylene, perfluorobutene, tetrafluoroethylene, trifluoroethylene, chlorotrifluoroethylene, and vinyl fluoride, and copolymerization refers to a reaction in which two or more compounds are polymerized into one substance under certain conditions.
[0152] The monomers constituting the acrylonitrile polymer in the present application include acrylonitrile, for example, it can be an acrylonitrile homopolymer, and homopolymerization refers to a polymerization reaction carried out by one organic monomer; of course, it can also be a copolymer formed by copolymerization of acrylonitrile with at least one of acrylates, acrylamides, vinyl esters, vinyl ethers, vinyl amides, vinyl ketones, styrenes, halogen-containing monomers (such as trichloroacetyl or tribromoacetyl), ionic monomers (such as 2-acrylamide-2-methylpropane sulfonic acid monomers), and basic monomers (such as 4-vinyl-_{3-sulfopropyl)pyridine indinate). Copolymerization refers to a reaction in which two or more compounds are polymerized into one substance under certain conditions.
[0153] The constituent monomers of the styrene acrylic polymer in the present application include styrene and acrylic acid, and of course other types of monomers may also be included to modify it, without specific limitation.
[0154] The constituent monomers of the pure acrylic polymer in the present application include acrylic acid, for example, it can be acrylic acid homopolymer, and of course it can also include other monomers, which are modified, and there is no specific limitation.
[0155] The constituent monomers of the styrene-butadiene polymer in the present application include styrene and butadiene, and of course other types of monomers may also be included to modify it, without specific limitation.
[0156] In one embodiment, the constituent monomers of the polyvinylidene fluoride polymer include vinylidene fluoride and hexafluoropropylene, and the molar ratio of vinylidene fluoride to hexafluoropropylene is 1:(0.03 to 0.5), preferably 1:(0.03 to 0.2); and / or, the constituent monomers of the styrene acrylic polymer include styrene and acrylic acid, and the molar ratio of styrene to acrylic acid is 5 / 1 to 1 / 5, preferably 2 / 1 to 1 / 2; and / or, the constituent monomers of the butadiene polymer include styrene and butadiene, and the molar ratio of styrene to butadiene is 3 / 1 to 1 / 3, preferably 1.5 / 1 to 1 / 1.5.
[0157] For example, in one embodiment, the constituent monomers of the polyvinylidene fluoride polymer include vinylidene fluoride and hexafluoropropylene, and the molar ratio of vinylidene fluoride to hexafluoropropylene is 1:(0.03 to 0.5), preferably, 1:(0.03 to 0.2); in one embodiment, the constituent monomers of the styrene acrylic polymer include styrene and acrylic acid, and the molar ratio of styrene to acrylic acid is 5 / 1 to 1 / 5, preferably, 2 / 1 to 1 / 2; in one embodiment, the constituent monomers of the butadiene polymer include styrene and butadiene, and the molar ratio of styrene to butadiene is 3 / 1 to 1 / 3, preferably, 1.5 / 1 to 1 / 1.5.
[0158] In the above 1: (0.03 to 0.5), the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 1: 0.03, 1: 0.05, 1: 0.1, 1: 0.2, 1: 0.3, 1: 0.4, 1: 0.5, etc., as well as the range values between any two of the above point values.
[0159] In the above 5 / 1 to 1 / 5, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 5 / 1, 4 / 1, 3 / 1, 2 / 1, 1, 1 / 2, 1 / 3, 1 / 4, 1 / 5, etc., as well as the range values between any two of the above point values.
[0160] In the above 3 / 1 to 1 / 3, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 3 / 1, 2 / 1, 1, 1 / 2, 1 / 3, etc., as well as the range values between any two of the above point values.
[0161] In one embodiment, the adhesive polymer comprises an emulsion type.
[0162] It can be understood that the first viscous polymer, the second viscous polymer, and the third viscous polymer respectively include but are not limited to emulsion types. The emulsion type refers to an emulsion state formed by the viscous polymer being dispersed in a dispersion medium (such as water) under the action of an emulsifier. The emulsion state has a good dispersion effect, and it is difficult for particles to agglomerate, which helps to evenly mix the slurry.
[0163] In one embodiment, the present application further provides a negative electrode plate, which includes a current collector, a primer layer and a negative electrode coating in sequence along a thickness direction, and the primer layer includes the binder as described above.
[0164] It can be understood that an active layer is formed by preparing a slurry of a binder, an active material, etc. and applying it to a current collector. Due to the evaporation of the solvent during the coating process, the binder tends to float under the action of capillary forces, surface tension, and concentration gradients. Binder floating refers to the redistribution of the evenly dispersed binder, so that the binder content in the place in contact with the current collector is reduced, and the binder floats to the surface of the slurry, resulting in insufficient bonding between the active material and the current collector, and there is a risk of demolding.
[0165] In order to improve the above problems, the present application directly uses a primer layer, which includes a binder. Compared with the active layer, the primer layer is thinner and there is no problem of the binder floating.
[0166] It can be understood that hard carbon particles are poorly regular and contain a large number of pores. The binder used in the present application has at least a bimodal particle size distribution. In the case of the same mass of binder, the binder with at least a bimodal particle size distribution forms more bonding sites. For example, in the bimodal particle size distribution, the particle size peak a is less than the particle size peak b. The binder with a bimodal particle size distribution includes a particle size peak a and a particle size peak b. The mass of the binder including the particle size peak a and the particle size peak b is the same as the mass of the binder consisting only of the particle size peak b. At this time, the number of binder particles whose bimodal particle size distribution includes the particle size peak a and the particle size peak b is greater than the number of binder particles whose unimodal particle size distribution includes only the particle size peak b. When the binder is evenly dispersed, the more binder particles there are, the more bonding sites are formed, which is beneficial to improving the bonding strength. In addition, the hard carbon pores include pores of different sizes. It is difficult for a binder with a single particle size to play a bonding role when facing large pores. Therefore, a binder with at least a bimodal particle size distribution is used so that the binder can exert better bonding properties when facing different pores.
[0167] like Figure 2 , which is a schematic structural diagram of a negative electrode plate 100 of the present application, wherein the base coating 20 is disposed on the current collector 10 , and the negative electrode coating 30 is disposed on a side of the base coating 20 away from the current collector.
[0168] In one embodiment, the thickness of the primer layer ranges from 1 um to 5 um, preferably from 1.5 um to 3 um.
[0169] The thickness of the undercoat layer satisfying the above range can improve the binding force between the active material and the current collector.
[0170] In the above-mentioned 1um to 5um, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 1um, 1.5um, 2um, 2.5um, 3um, 4.5um, 4um, 4.5um, 5um, etc., and the range values between any two of the above-mentioned point values.
[0171] In one embodiment, the mass percentage of the binder in the primer layer to the total mass of the primer layer is 10% to 70%, preferably, 20% to 50%.
[0172] Define the total mass of the primer layer as M, the mass of the binder as m1, and the calculation formula for the percentage of the mass of the binder in the primer layer to the total mass of the primer layer is (m1÷M)×100%.
[0173] The percentage of the mass of the binder in the primer layer to the total mass of the primer layer satisfies the above range, which can improve the bonding performance of the binder. Specifically, when the mass of the binder accounts for too small a percentage of the total mass of the primer layer, the problem of poor adhesion is improved, and when the mass of the binder accounts for too large a percentage of the total mass of the primer layer, the problem of deteriorated conductivity between the current collector and the active layer is improved.
[0174] In the above 10% to 70%, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 10%, 20%, 30%, 40%, 50%, 60%, 70%, etc., and the range values between any two of the above point values.
[0175] In one embodiment, the primer layer includes a conductive agent, a dispersant and a binder, and the mass ratio of the conductive agent, the dispersant and the binder is in the range of (30 to 80): (1 to 10): (10 to 70).
[0176] Conductive agent is used to ensure that the electrode has good charge and discharge performance. A certain amount of conductive material is usually added during the production of the electrode. It collects microcurrents between active materials and between active materials and current collectors to reduce the contact resistance of the electrode and accelerate the movement rate of electrons. It can also effectively increase the migration rate of lithium ions in the electrode material, thereby improving the charge and discharge efficiency of the electrode.
[0177] Dispersant has dispersing properties, which enables the mixed components to be effectively dispersed.
[0178] The primer layer includes a conductive agent, a dispersant and a binder. The mass ratio of the conductive agent, the dispersant and the binder satisfies the above range, which can improve the conductivity and adhesion of the primer layer.
[0179] In the above (30 to 80): (1 to 10): (10 to 70), the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 30:1:10, 40:3:20, 50:5:30, 60:6:40, 70:8:50, 80:10:70, etc., as well as the range values between any two of the above point values.
[0180] In one embodiment, the porosity of the negative electrode coating ranges from 30% to 70%, preferably, from 35% to 60%.
[0181] The porosity range of the negative electrode coating satisfies the above range, which can improve the bonding between the negative electrode material and the current collector.
[0182] In the above 30% to 70%, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, etc., as well as the range values between any two of the above point values.
[0183] In one embodiment, the present application also provides a method for preparing a negative electrode plate, comprising: mixing a conductive agent, a dispersant, and a binder to prepare a primer slurry; applying the primer slurry to a current collector to obtain a primer layer; applying the negative electrode slurry to the primer layer to obtain a negative electrode plate.
[0184] like Figure 1 As shown, in the process of preparing the negative electrode sheet, the conductive agent, the dispersant and the binder are mixed to prepare the primer slurry; the primer slurry is applied to the current collector to obtain the primer layer; the negative electrode slurry is applied to the primer layer to obtain the negative electrode sheet.
[0185] In one embodiment, the present application further provides a battery, which includes the negative electrode plate as described above, or includes the negative electrode plate obtained by the preparation method of the negative electrode plate as described above.
[0186] Since the battery adopts all the technical solutions of all the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here. The battery type of this application is not limited, for example, it can be a lithium secondary battery or a sodium secondary battery, which is not specifically limited.
[0187] It is understandable that batteries include secondary batteries, battery modules, and battery packs.
[0188] In one embodiment, the present application further provides an electrical device, which includes the battery as described above.
[0189] Since the battery adopts all the technical solutions of all the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0190] In addition, the battery (secondary battery, battery module, battery pack) and the electric device of the present application will be described below with reference to the drawings as appropriate.
[0191] In one embodiment of the present application, a secondary battery is provided.
[0192] Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through. The separator is the separator improved above in this application.
[0193] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector.
[0194] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0195] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0196] In some embodiments, when the secondary battery is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0197] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.
[0198] In the list of positive electrode materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.
[0199] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0200] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0201] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0202] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0203] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0204] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0205] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0206] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0207] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0208] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0209] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs.
[0210] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0211] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0212] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0213] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0214] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected.
[0215] In some embodiments, the material of the diaphragm can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The diaphragm can be a single-layer film or a multi-layer composite film, without particular limitation. When the diaphragm is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0216] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0217] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0218] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0219] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 3 The battery cell 5 is a square structure as an example.
[0220] In some embodiments, reference Figure 4 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the diaphragm can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0221] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0222] Figure 5 4 is an example of a battery module. Figure 5 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0223] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0224] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0225] Figure 6 and Figure 71 is a battery pack 1 as an example. Figure 6 and Figure 7 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0226] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0227] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0228] Figure 8 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0229] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0230] Example
[0231] Example 1
[0232] Preparation of the first viscous polymer:
[0233] Preparation of polyvinylidene fluoride with D1 of 10 nm: (1) injecting water into a 100L high-pressure polymerization kettle; (2) performing vacuum extraction and oxygen removal for multiple times, and then replacing with high-purity nitrogen to make the oxygen content in the polymerization kettle less than 50ppm, and adding 100g of surfactant ammonium perfluorooctanoate; (3) adding vinylidene fluoride monomer (VDF) to 5.5MPa, starting stirring at 90RPM, heating the polymerization kettle to 110°C, adding 30g of initiator di-tert-butyl peroxide, and adding 60g of the molecular weight regulator, wherein the ratio of dodecanethiol is 0.5% and the ratio of chloroacetone is 99.5%; (4) when the pressure in the kettle begins to drop, continuously adding VDF to maintain the pressure in the kettle at 5.5MPa, and slowly adding the molecular weight regulator to 120g; (5) maintaining the reaction pressure at 5.5Mpa, adding 12.5kg of VDF, and continuously sampling and testing the D1 of polyvinylidene fluoride during the reaction until D1 meets the requirements, and then stopping the reaction.
[0234] Preparation of the Second Viscous Polymer:
[0235] Preparation of polyvinylidene fluoride with D2 of 400 nm: The polyvinylidene fluoride was prepared by the same method as above. During the reaction, samples were continuously taken to test the D2 of the polyvinylidene fluoride until D2 met the requirements, and the reaction was stopped.
[0236] Preparation of the third viscous polymer:
[0237] Preparation of polyvinylidene fluoride with D3 of 1000 nm: polyvinylidene fluoride was prepared by the same method as above. During the reaction, samples were continuously taken to test the D3 of polyvinylidene fluoride until D3 met the requirements, and the reaction was stopped.
[0238] The prepared first viscous polymer, second viscous polymer, and third viscous polymer are mixed at a mass ratio of 1:1:1 to obtain a binder.
[0239] Preparation of base coating:
[0240] Conductive agent SP (conductive carbon black), dispersant CMC (sodium carboxymethyl cellulose) and the above-prepared binder were dry-mixed at a mass ratio of 40:5:55 at 1000 r / min for 15 minutes, and then dispersed in water for 60 minutes to prepare a primer slurry.
[0241] The primer slurry is coated on the surface of the copper foil current collector by a gravure printing machine, the coating thickness of the primer slurry is controlled at 3 μm, and a primer layer is formed on the copper foil current collector after drying.
[0242] Preparation of negative electrode sheet:
[0243] 93.8% of hard carbon, a thickener of sodium carboxymethyl cellulose (CMC), 1.4% of styrene-butadiene rubber (SBR), a binder, 2.6% of conductive carbon SP, and 0.2% of 1.3 butanediol are dissolved in deionized water according to a mass ratio, mixed evenly to obtain a negative electrode slurry, and the slurry is coated on the base coating of the negative electrode current collector copper foil, and cold pressed to obtain a negative electrode sheet.
[0244] Example 2 to Example 11
[0245] On the basis of Example 1, the type, particle size and other parameters of the emulsion binder were adjusted to obtain Examples 2 to 11.
[0246] Preparation of (acrylonitrile) polyacrylonitrile in Example 4:
[0247] Preparation of the first viscous polymer: Preparation of polyacrylonitrile with D1 of 100 nm: 140 g of deionized water and 60 g of acrylonitrile monomer are added to a polymerization container with a stirring device, nitrogen is introduced, and the temperature is raised. When the polymerization system temperature is 40°C, 0.18 g of potassium persulfate, 1.08 g of sodium bisulfite, and 0.001 g of ferrous sulfate are added dropwise, and the addition is completed within 30 min. After the temperature is raised to 50°C, polymerization is carried out, and the D3 of polyacrylonitrile is tested during the polymerization process until D3 meets the requirements, and a composite terminator is added to stop the reaction. Wherein: the composite terminator configuration process is to add 0.4 g of polyvinyl alcohol with a degree of alcoholysis of 80% into deionized water, stir and dissolve at 75°C, until the polyvinyl alcohol is completely dissolved, then add 0.2 g of pentaerythritol ester and 0.015 g of EDTA, stir evenly, and then use a high-speed shear emulsifier for shear emulsification, the shear rate is 10000 rpm, and the shear time is 15 min. After shearing, a composite terminator is obtained.
[0248] Preparation of the second viscous polymer: Preparation of polyacrylonitrile with D2 of 300 nm: Polyacrylonitrile was prepared by the same method as above. During the reaction, samples were continuously taken to test the D2 of polyacrylonitrile until D2 met the requirements, and the reaction was stopped.
[0249] Preparation of the third viscous polymer: Preparation of polyacrylonitrile with D3 of 600 nm: Polyacrylonitrile was prepared by the same method as above. During the reaction, samples were continuously taken to test the D3 of polyacrylonitrile until D3 met the requirements, and the reaction was stopped.
[0250] The prepared first viscous polymer, second viscous polymer, and third viscous polymer are mixed at a mass ratio of 1:1:1 to obtain a binder.
[0251] Preparation of (styrene-acrylic) polystyrene-acrylic polymer in Example 5:
[0252] Preparation of the first viscous polymer: Preparation of a polystyrene-acrylic acid polymer with a D1 of 140 nm: Styrene and acrylic acid are mixed in a molar ratio of 20:1, and after being fully stirred and mixed at room temperature, sodium dodecylbenzene sulfonate (the mass ratio of sodium dodecylbenzene sulfonate to styrene monomer is 0.02:1) is added for pre-emulsification, and then the temperature is slowly raised. During the process of raising the temperature from 50°C to 80°C, 3 parts of potassium persulfate solution are added dropwise in 3 times, and then the temperature is raised to 85°C, and the reaction is kept warm for 2 hours, and then 4 parts of potassium persulfate solution are added dropwise to continue the reaction. During the reaction, the D1 of the polystyrene-acrylic acid polymer is tested until D1 meets the requirements and the reaction is stopped; the mass ratio of potassium persulfate in the 7 parts of potassium persulfate solution to the mass ratio of styrene monomer is 0.016:1.
[0253] Preparation of the second viscous polymer: Preparation of polystyrene-acrylic acid polymer with D2 of 400 nm: The polystyrene-acrylic acid polymer was prepared by the same method as above. During the reaction, samples were continuously taken to test the D2 of the polystyrene-acrylic acid polymer until D2 met the requirements, and the reaction was stopped.
[0254] Preparation of the third viscous polymer: Preparation of polystyrene-acrylic acid polymer with D3 of 800 nm: The polystyrene-acrylic acid polymer was prepared by the same method as above. During the reaction, the D3 of the polystyrene-acrylic acid polymer was continuously sampled and tested until D3 met the requirements, and the reaction was stopped.
[0255] The prepared first viscous polymer, second viscous polymer, and third viscous polymer are mixed at a mass ratio of 1:1:1 to obtain a binder.
[0256] Preparation of (pure acrylic acid) acrylic acid polymer in Example 6:
[0257] Preparation of the first viscous polymer: Preparation of acrylic acid polymer with D1 of 100 nm: Prepare polyacrylic acid aqueous solution by solution polymerization of acrylic acid using sodium peroxodisulfate as initiator and sodium hypophosphite as chain transfer agent. Test the D1 of the acrylic acid polymer during the polymerization reaction until D1 meets the requirements and stop the reaction.
[0258] Preparation of the second viscous polymer: An acrylic polymer with a D2 of 160 nm was prepared by the same method as above.
[0259] Preparation of the third viscous polymer: an acrylic polymer with a D3 of 500 nm was prepared by the same method as above.
[0260] The prepared first viscous polymer, second viscous polymer, and third viscous polymer are mixed at a mass ratio of 1:1:1 to obtain a binder.
[0261] Preparation of (butylene-styrene) butadiene-styrene copolymer in Example 7:
[0262] Preparation of the first viscous polymer: Preparation of a butadiene-styrene copolymer with a D1 of 120 nm: 65 parts (parts by mass, the same below) of butadiene, 35 parts of styrene, 200 parts of water, 5 parts of potassium disproportionate rosin acid emulsifier, and 0.8 parts of potassium persulfate were mixed, and the mixture was emulsified at a speed of 500 rpm for 20 minutes to complete the dispersion, and then the temperature was raised to 50°C for free radical emulsion polymerization. During the reaction, samples were continuously taken to test the test D1 of the butadiene-styrene copolymer until D1 met the requirements and the reaction was stopped.
[0263] Preparation of the second viscous polymer: a butadiene-styrene copolymer with a D2 of 250 nm was prepared by the same method as above.
[0264] Preparation of the third viscous polymer: a butadiene-styrene copolymer with a D3 of 1000 nm was prepared by the same method as above.
[0265] The prepared first viscous polymer, second viscous polymer, and third viscous polymer are mixed at a mass ratio of 1:1:1 to obtain a binder.
[0266] Comparative Examples 1 to 7
[0267] Based on the examples, the particle size of the emulsion binder and the porosity of the negative electrode coating were adjusted to obtain Comparative Examples 1 to 7.
[0268] Pole piece adhesion test
[0269] The peel strength test was conducted using the test method for flexible materials to rigid materials in GB / T 2790-1995 Adhesive 180° Peel Strength Test Method.
[0270] Table 1 Experimental data list
[0271]
[0272]
[0273] It can be seen from the table above that when the binder is composed of a plurality of viscous polymers with different particle size distributions, the bonding force of the pole piece is improved. It can be seen from the examples and comparative examples that the bonding effect of the pole piece of the binder with a single particle size distribution is not as good as that of the binder with multiple particle size distributions.
[0274] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the contents of the present invention's specification and drawings, or directly / indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A binder, characterized in that: The binder has at least a bimodal particle size distribution.
2. The adhesive according to claim 1, characterized in that The adhesive comprises a first viscous polymer and a second viscous polymer, wherein the Dv50 value of the first viscous polymer is defined as D1, and the Dv50 value of the second viscous polymer is defined as D2, satisfying D1<D2, preferably, 0nm<(D2-D1)≤390nm, and further preferably, 100nm≤(D2-D1)≤350nm; And / or, the adhesive comprises a first viscous polymer, and a Dv50 value of the first viscous polymer is defined as D1, satisfying 10nm≤D1<150nm, preferably, 50nm≤D1<150nm; And / or, the adhesive includes a second viscous polymer, the Dv50 value of the second viscous polymer is D2, and satisfies 150nm≤D2≤400nm.
3. The adhesive according to claim 1 or 2, characterized in that The at least bimodal particle size distribution comprises a first particle size peak and a second particle size peak, wherein the first particle size peak is smaller than the second particle size peak, and preferably, the difference between the first particle size peak and the second particle size peak is in a range of greater than 0 nm and less than or equal to 390 nm, preferably, 100 nm to 350 nm; And / or, the at least bimodal particle size distribution comprises a first particle size peak value, the first particle size peak value has a range value of greater than or equal to 10 nm and less than 150 nm, preferably, greater than or equal to 50 nm and less than 150 nm; And / or, the at least bimodal particle size distribution comprises a second particle size peak, wherein the second particle size peak has a value in the range of 150 nm to 400 nm.
4. The adhesive according to claim 2, characterized in that The adhesive further comprises a third viscous polymer, the Dv50 value of the third viscous polymer is D3, satisfying D2<D3, preferably, 0nm<(D3-D2)≤850nm, and further preferably, 250nm≤(D3-D2)≤650nm ; And / or, the adhesive further includes a third viscous polymer, the Dv50 value of the third viscous polymer is D3, and satisfies 400nm<D3≤1000nm, preferably, 400nm<D3≤800nm.
5. The adhesive according to claim 3, characterized in that The at least bimodal particle size distribution further comprises a third particle size peak value, the third particle size peak value is greater than the second particle size peak value, preferably, the range value of the difference between the third particle size peak value and the second particle size peak value is greater than 0 nm and less than or equal to 850 nm, preferably, 250 nm to 650 nm; And / or, the at least bimodal particle size distribution further includes a third particle size peak value, the range value of the third particle size peak value is greater than 400 nm and less than or equal to 1000 nm, preferably, greater than 400 nm and less than or equal to 800 nm.
6. The adhesive according to claim 2 or 4, characterized in that Define the mass of the first viscous polymer as m1, and the mass of the second viscous polymer as m2, then m1 / m2=1 / 9 to 9, preferably, m1 / m2=1 / 3 to 3.
7. The adhesive according to claim 6, characterized in that The mass of the third viscous polymer is defined as m3, then (m1+m2) / m3=1 / 9 to 9, preferably, (m1+m2) / m3=1 / 3 to 3.
8. The adhesive according to any one of claims 1 to 7, characterized in that The glass transition temperature of the binder is -50°C to 60°C, preferably, -40°C to 30°C.
9. The adhesive according to any one of claims 1 to 8, characterized in that The adhesive polymer includes at least one of polyvinylidene fluoride polymers, acrylonitrile polymers, styrene acrylic polymers, pure acrylic polymers, and styrene butadiene polymers, and preferably includes styrene butadiene polymers and / or styrene acrylic polymers.
10. The adhesive according to claim 9, characterized in that The constituent monomers of the polyvinylidene fluoride polymer include vinylidene fluoride, or further include at least one of hexafluoropropylene, pentafluoropropylene, tetrafluoropropylene, trifluoropropylene, perfluorobutene, tetrafluoroethylene, trifluoroethylene, trifluorochloroethylene, and vinyl fluoride; And / or, the monomers constituting the acrylonitrile polymer include acrylonitrile, or further include at least one of acrylates, acrylamides, vinyl esters, vinyl ethers, vinyl amides, vinyl ketones, styrenes, halogen-containing monomers, ionic monomers, and basic monomers; And / or, the constituent monomers of the styrene acrylic polymer include styrene and acrylic acid; And / or, the constituent monomers of the pure acrylic polymer include acrylic acid; And / or, the constituent monomers of the styrene-butadiene polymer include styrene and butadiene.
11. The adhesive according to claim 9 or 10, characterized in that The constituent monomers of the polyvinylidene fluoride polymer include vinylidene fluoride and hexafluoropropylene, and the molar ratio of the vinylidene fluoride to the hexafluoropropylene is 1:(0.03 to 0.5), preferably, 1:(0.03 to 0.2); And / or, the constituent monomers of the styrene acrylic polymer include styrene and acrylic acid, and the molar ratio of the styrene to the acrylic acid is 5 / 1 to 1 / 5, preferably, 2 / 1 to 1 / 2; And / or, the constituent monomers of the styrene-butadiene polymer include styrene and butadiene, and the molar ratio of the styrene to the butadiene is 3 / 1 to 1 / 3, preferably, 1.5 / 1 to 1 / 1.
5.
12. The adhesive according to any one of claims 1 to 11, characterized in that Adhesive polymers include emulsion types.
13. A negative electrode plate, characterized in that: The negative electrode sheet comprises a current collector, a primer layer and a negative electrode coating in sequence along a thickness direction, and the primer layer comprises a binder as claimed in any one of claims 1 to 11.
14. The negative electrode sheet according to claim 13, characterized in that: The thickness of the primer layer ranges from 1 um to 5 um, preferably from 1.5 um to 3 um.
15. The negative electrode sheet according to claim 13 or 14, characterized in that: The mass percentage of the binder in the primer layer to the total mass of the primer layer is 10% to 70%, preferably 20% to 50%.
16. The negative electrode sheet according to any one of claims 13 to 15, characterized in that: The primer layer includes a conductive agent, a dispersant and the binder, and the mass ratio of the conductive agent, the dispersant and the binder is in the range of (30 to 80): (1 to 10): (10 to 70).
17. The negative electrode sheet according to any one of claims 13 to 16, characterized in that: The porosity of the negative electrode coating ranges from 30% to 70%, preferably, from 35% to 60%.
18. A method for preparing a negative electrode sheet according to any one of claims 13 to 17, characterized in that: include: Mixing a conductive agent, a dispersant, and a binder to prepare a primer slurry; Applying the primer slurry to a current collector to obtain a primer layer; The negative electrode slurry is applied to the undercoat layer to obtain a negative electrode sheet.
19. A battery, characterized in that: The battery comprises a negative electrode sheet as claimed in any one of claims 13 to 17; Alternatively, a negative electrode sheet obtained by the method for preparing a negative electrode sheet as claimed in claim 18.
20. An electrical device, characterized in that: The electrical device comprises the battery as claimed in claim 19.